Rural Women’s Invisible Work in Census and State Rural Development Plans: The Argentinean Patagonian Case - Paula Gabriela Núñez; Carolina Lara Michel; Paula Alejandra Leal Tejeda; Martín Andrés Núñez (Land, 2020)
This article reviews the invisibility and the recognition of rural female work in the Patagonian region of Argentina over time. The analysis is carried out based on (a) the systematisation of research articles (b) a historical study of censuses, and (c) the systematisation of rural development plans related to the subject. The article adopts an ecofeminist perspective. The results have been organised into four sections. (1) An overview of the later Patagonian integration; (2) the work of Patagonian women in history; (3) the recognition of rural production in censuses; (4) Patagonian family farming. We found out that the metaphors that relate women with the land are used to deny both rural female work and the family land use. One of its consequences is that Patagonia has become one of the most affected by extractivism. We conclude reviewing the forms of economic and political recognition, which could intervene in future planning.